El subsidio familiar: un recurso público y su control (2023)
Law 21 of 1982 (Congress of the Colombia, 1982, art. 1) authorized the Ministry of National Education to collect the parafiscal contribution, corresponding to 1% of the payrolls of public entities of the National, Departmental, District and Municipal order, destined for "Industrial Schools and Technical Institutes", in Article 1 of this order creates the family subsidy, which is a social benefit payable in money, kind, and services to medium- and low-income workers, in proportion to the number of dependents, and its fundamental objective is to alleviate the economic burdens that the maintenance of the family represents, as the basic nucleus of society.